An american tragedy - Dreiser, Theodore 1871-1945; Leipold, John 1888-1970; Rainger, Ralph 1901-1942 (Universal Studios, 2023)
"Ein junger Büroangestellter erhofft sich von der Heirat mit einem reichen Mädchen den Aufstieg in höhere Kreise; die junge Arbeiterin, die ein Kind von ihm erwartet, steht ihm dabei jedoch im Wege. Drama nach Theodore Dreiser, das Milieu und Charaktere intensiv herausarbeitet. (Die Vorlage wurde 1951 unter dem Titel "Ein Platz an der Sonne" erneut verfilmt.)" [filmdienst.de]
Original: USA 1931
Indicator limited edition special features: 2019 restoration from a 4K scan ; original mono audio ; audio commentary with film historian Josh Nelson (2023) ; Josef von Sternberg oral history (1958, 27 mins): rare archival audio recording of the celebrated filmmaker in conversation with George Pratt ; Lee Garmes oral history (1958, 89 mins): rare archival audio recording of the cinematographer in conversation with Pratt ; An american picture (2023, 29 mins): extensive discussion of An american tragedy by the writer and film programmer Tony Rayns ; Nurture & nature (2023, 8 mins): video essay by film historian Tag Gallagher ; image gallery: promotional and publicity materials ; new and improved English subtitles for the deaf and hard of hearing ; limited edition exclusive 40-page booklet with a new essay by Imogen Sara Smith, Jeff Billington on Sergei Eisenstein’s proposed Hollywood adaptation of An american tragedy, extracts from Josef von Sternberg’s memoir Fun in a Chinese laundry, an archival article on Theodore Dreiser’s response to the film, and film credits ; world premiere on Blu-ray ; limited edition of 3,000 copies for the UK
Bildformat 1.19:1
Keywords: Film; Blu-Ray-Disc